2019
DOI: 10.1016/j.bbi.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity impact on gut microbiota and inflammatory response to stress during pregnancy

Abstract: Background: Adverse childhood experiences (ACEs), such as abuse or chronic stress, program an exaggerated adult inflammatory response to stress. Emerging rodent research suggests that the gut microbiome may be a key mediator in the association between early life stress and dysregulated glucocorticoid-immune response. However, ACE impact on inflammatory response to stress, or on the gut microbiome, have not been studied in human pregnancy, when inflammation increases risk of poor outcomes. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 103 publications
(151 reference statements)
6
105
2
Order By: Relevance
“…Moreover, the abundance of Bifidobacterium was positive to antioxidative capacity [62]. Members of the Dialister genus are asaccharolytic obligately anaerobic gram-negative coccobacilli, and negatively associated with pro-inflammatory cytokine response [63,64]. Streptococcus and Escherichia-Shigella are both pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the abundance of Bifidobacterium was positive to antioxidative capacity [62]. Members of the Dialister genus are asaccharolytic obligately anaerobic gram-negative coccobacilli, and negatively associated with pro-inflammatory cytokine response [63,64]. Streptococcus and Escherichia-Shigella are both pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Going forward, prospective data in African American women with healthy versus adverse outcomes would inform our understanding of the potential role of immune dysregulation in racial disparities in birth outcomes among women at high risk for chronic stress and immune activation. Additionally, investigation into the role of early life experiences 56 and coping mechanisms developed over the life course 53 may offer insight into protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…These observations in humans are reflected in experimental animal models of early-life stress, which have long been used to model both psychological and gastrointestinal disorders (O'Mahony et al, 2011). Moreover, a number of recent studies have demonstrated links between prenatal stress (including maternal anxiety) or early-life adversity (i.e., postnatal stress) and alterations in the human microbiota across the life span (Callaghan et al, in press;D'Agata et al, 2019;Hantsoo et al, 2019;Hemmings et al, 2017;Hu et al, 2019;Labus et al, 2017;Michels et al, 2019;Zijlmans et al, 2015).…”
Section: Box 1 Measuring the Microbiotamentioning
confidence: 99%